Refined pharmacophore features for virtual screening of human thromboxane A2 receptor antagonists. (June 2020) - Hu, Baichun; Joseph, Johnson; Geng, Xiaohui; Wu, Yiheng; Suleiman, Muhammad R.; Liu, Xinyue; Shi, Jiyue; Wang, Xiujun; He, Zhicheng; Wang, Jian; Cheng, Maosheng
Graphical abstract: Highlights: The pharmacophores were established using newly resolved crystal structures of human thromboxane A2 receptor. Structure-based virtual screening was performed to identify lead molecules with stable dynamics trajectory. Safety of the top molecules was analyzed using publicly available wares like pkCSM and SwissADME. Binding free energies of VS this were predicted using MM/GBSA. Abstract: For a long time, the structural basis of TXA2 receptor is limited due to the lack of crystal structure information, till the release of the crystal structure of TXA2 receptor, which deepens our understanding about ligand recognition and selectivity mechanisms of this physiologically important receptor. In this research, we report the successful implementation in the discovery of an optimal pharmacophore model of human TXA2 receptor antagonists through virtual screening. Structure-based pharmacophore models were generated based on two crystal structures of human TXA2 receptor (PDB entry 6IIU and 6IIV). Docking simulation revealed interaction modes of the virtual screening hits against TXA2 receptor, which was validated through molecular dynamics simulation and binding free energy calculation. ADMET properties were also analyzed to evaluate the toxicity and physio-chemical characteristics of the hits. The research would provide valuable insight into the binding mechanisms of TXA2 receptor antagonists and thus be helpful for designing novel antagonists.